Short Notices (Heythrop journal, 2001)
Books reviewed: Patrick H. Alexander, et al(ed), The SBL Handbook of Style for Ancient Near Eastern, Biblical and Early Christian Studies C. E. B. Cranfield, On Romans and Other New Testament Essays The Christ and the Spirit: Collected Essays of James D. G. Dunn. Paul Heelas (ed), Religion, Modernity and Postmodernity John P. Newport, The New Age Movement and the Biblical Worldview: Conflict and Dialogue Janet Hamilton and Bernard Hamilton, Christian Dualist Heresies in the Byzantine World, c. 650–1405: Selected Sources Lotte Kéry, Canonical Collections of the Early Middle Ages (c. 400–1140): A Bibliographical Guide to the Manuscripts and Literature Gilbert Dahan, The Christian Polemic against the Jews in the Middle Ages Gary Macy, Treasures from the Storeroom: Medieval Religion and the Eucharist Eric Cahm, The Dreyfus Affair in French Society and Politics Alistair Kee, Nietzsche Against the Crucified Mary Jo Iozzio, Self-Determination and the Moral Act: A Study of the Contributions of Odon Lottin, O.S.B. Peter Glasner and Harry Rothman (eds), Genetic Imaginations: Ethical, Legal and Social Issues in Human Genome Research Frank J. Coppa (ed), Encyclopedia of the Vatican and Papacy